Measuring the influence of factors on destination brand loyalty – A case study of Binh Thuan province - Huynh, Nhựt Nghĩa (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
The research objective of the article is to measure the level of influence of factors on destination brand loyalty in the case study of Binh Thuan province, thereby proposing some implications for destination branding. The study conducted a survey of 500 tourists who have been to Binh Thuan. The research results show that the factor with the greatest influence on Binh Thuan destination brand loyalty is: Brand perception, followed by Brand association. In which, Brand awareness has an impact on Brand perception and Brand association but does not affect brand loyalty at a significance level of 0.5%. Based on the research results, some implications are proposed for building the Binh Thuan destination brand image such as: Building and upgrading tourism infrastructure; Improving service quality, training tourism human resources; Building positive links with strategic partners in the industry.